Stroke and associated comorbidities in Southeast Asian countries - Aishika Datta; Soumya Akundi; Kaveri Wagh; Gangadhar Bhurle; Deepaneeta Sarmah; Arvind Sharma; Sudhir Shah; Anupom Borah; Shailendra Saraf; Pallab Bhattacharya (Neuroprotection)
Abstract Stroke, a leading cause of mortality and morbidity worldwide, is a complex cerebrovascular disease. Stroke risk factors are diverse, encompassing age, sex, and ethnicity. Comorbid conditions, including hypertension, hyperglycemia, hyperlipidemia, and atrial fibrillation, exacerbate stroke outcomes, contributing to the overall stroke burden within populations. In addition to these factors, lifestyle‐related diseases can impact individuals across all age groups, and often include as comorbidities linked to stroke. Socioeconomic conditions, healthcare access, and the quality of clinical data significantly influence the prevalence of comorbidities. Asia, the largest continent and home to 60% of the world's population, includes many developing nations undergoing diverse economic transitions. In Southeast Asian countries, stroke prevalence is high, imposing a substantial burden on healthcare systems and economies. Research disparities in stroke are often attributed to insufficient demographic data on comorbidities. Hence, the review discusses all previously published results of hospital‐based studies and data from national registries. It has been noticed that due to insufficient documentation on stroke‐related comorbidities in various developing countries of Southeast Asia, stroke management becomes difficult. Therefore, this review aims to discuss the association between various comorbidities and stroke, with special emphasis on the incidence and prevalence of stroke burden in Southeast Asian countries.